Dynamics of Poverty and Reduction Programs (Empirical Analysis of Data Panels in 26 Sub-District in Klaten Regency) - Wahyuni, Wiwik Sri; Arif, Muhammad (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The unequal development causes the number of poor people to increase in several subdistricts in Klaten district. Various alleviation programs organized by the government are able to reduce the number of poor people. However, the decline seems slow. These programs include: PKH (Family Hope Program), Dana Desa and PIP (Smart Indonesia Program). This study aims to analyse the dynamics of poverty and its alleviation program in 26 sub-districts in Klaten Regency in 2018, 2019 and 2020. This study uses secondary data with panel data regression analysis techniques using the best model Fixed Effect Model (FEM). The results showed that the highest poverty was in Trucuk District. Based on the results of panel data analysis, is can be explained that the Family Hope Program (PKH) has a positive and significant effect, the Village Fund has a negative and significant effect, while the Indonesian Program has a negative and insignificant effect.